I read [expr.ref#2] which includes the following sentence:

> The expression E1->E2 is converted to the equivalent form (*(E1)).E2

My question is, does this mean that "every" expression that has the form E1->E2  will be converted to (*(E1)).E2. I mean it is not clear to me in what situations/contexts does the above sentence hold?

For example, suppose we have a class that overloads operator* but does not overload operator-> then if we use operator-> with an object of that class type, then that expression will be first converted to (*(E1)).E2 form?

#include <iostream>  
struct A {
    int foo = 1, bar =2;
};

struct B {
    A a{};
    
    A& operator* () 
    {
        return a; 
    }

}; 

int main()
{
    B b{};
    int x = b->foo; //i know this will give error because there is no overloaded operator-> 
                   //but according to [expr.ref#2] shouldn't b->foo be first converted to (*(b)).foo
                   //and then the overloaded operator* should be used  
      
}

As you can see in the above program, `b->foo;` gives an error because the class `B` has not overloaded operator-> . But according to [expr.ref#2] the expression b->foo should be converted to (*(b)).foo and then the operator* could be used.

So I want to know what exactly does [expr.ref#2] mean when it said " The expression E1->E2 is converted to the equivalent form (*(E1)).E2 ". Does this conversion supposed to happen only after `E1->E2` is valid or before. Is a CWG issue required for this or I just did not read/interpret it correctly.

Regards,
Sean(ASR)